An Analysis of Students’ Grammatical Errors in Writing Procedure Texts - Husnayaini, Ihda; Rizki, M Thaib; Savitri, Chindy (EEdJ: English Education Journal, 2021)
This study investigated the common types of grammatical errors made by 3rd grade of secondary male and female students at SMP Muhammadiyah Pangkalpinang in writing procedure texts and to find out whether there was any significant difference in the errors committed by the students when grouped according to gender. The researcher specified this study in writing procedure text which focused on their errors. The research method used was quantitative. The samples of this study were 30 students that were taken from 9th grade of SMP Muhammadiyah Pangkalpinang. The data was obtained from the sentences written by the students and by means of the test. In this study, the result of the test was analyzed by paired sample t-test. In accordance with the result analysis, the study revealed two major findings. The result showed that there was a significant difference in the errors committed by the students when grouped according to gender. Therefore, the data further means that gender affects the number, and percentage of errors committed by the students.